Towel rack surface corrosion-resistant spraying process

Through the nano spraying process, the application of composite water-based polyurethane emulsion and modified graphite phase carbon nitride materials on the surface of the towel rack is solved, and the problem of anti-corrosion in humid environments is achieved, high corrosion resistance, superhydrophobicity, antibacteriality and thermal stability is achieved, which extends the service life and reduces the disadvantage rate.

CN119565890APending Publication Date: 2025-03-07JIANGXI AVONFLOW HVAC TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411755872.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing towel racks are difficult to solve in humid environments, and common paint spraying has defects such as rough surface and orange peel, which affects the product's adhesion and wear resistance.

Method used

Using nano spraying technology, a high-performance protective coating is formed by mixing composite aqueous polyurethane emulsion with modified graphite phase carbon nitride and other materials, spraying on the surface of the pretreated towel rack, and photocuring is used to form a high-performance protective coating.

Benefits of technology

The high corrosion resistance, superhydrophobicity, antibacteriality and thermal stability of towel racks are achieved, which greatly extends the service life of towel racks and reduces the defect rate of products.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of corrosion resistance, in particular to a towel rack surface corrosion-resistant spraying process, which is characterized in that a towel rack is treated in a spraying manner, and modified graphite phase carbon nitride is introduced into a protective coating as a filler by performing component design on the coating for spraying and then performing light curing treatment; the preparation method comprises the following steps: by taking tyrosine and thiourea as precursors, preparing graphite phase carbon nitride nanosheets by a microwave method, then preparing a zinc oxide-graphite phase carbon nitride binary composite nanomaterial by a hydrothermal method, carrying out double-bond treatment on composite graphite phase carbon nitride by utilizing vinyltriethoxysilane, and then grafting long-chain alkyl modified polysilazane containing double bonds; the preparation method comprises the following steps: by taking castor oil as a raw material, synthesizing a prepolymer together with isophorone diisocyanate under the action of a catalyst, taking 3-dimethylamino-1, 2-propylene glycol as a chain extender, taking 2, 2-dimethylolpropionic acid as a hydrophilic chain extender, and taking hydroxyethyl methylacrylate and hydroxylated long-chain alkyl modified polysilazane as end-capping reagents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of corrosion resistance technology, in particular to a corrosion-resistant spraying process for the surface of a towel rack. Background Art

[0002] A towel rack generally refers to a rack used to store towels, bath towels, sundries, etc. With changes in the market, existing consumers have increasing demands for towel racks with functions such as heating, drying, disinfection, and antibacterial. Existing towel racks are mostly made of metal, and the corrosion resistance of metals in humid environments has always been a hot topic in industry research.

[0003] With the progress of society and the enhancement of environmental awareness, nano-spraying has broad application prospects in the fields of electronics, optics, etc. Nano-spraying uses advanced equipment and materials to directly spray on the surface of the object to be coated, thereby improving the high-gloss texture and appearance of the object to be coated, and improving the adhesion and wear resistance of the product. Therefore, the use of nano-spraying to improve the corrosion resistance of metal towel racks is gradually emerging. Compared with the common direct coating of paint, nano-spraying will reduce the probability of defects such as surface roughness, orange peel, particles, bubbles, pinholes, color difference, etc., thereby reducing the defective rate of products. Summary of the invention

[0004] The purpose of the present invention is to provide a corrosion-resistant spraying process for the surface of a towel rack to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A corrosion-resistant spraying process for the surface of a towel rack comprises the following steps:

[0007] S1: frosting, polishing, cleaning and drying the towel rack in sequence to obtain a pre-treated towel rack;

[0008] S2: Mix the composite waterborne polyurethane emulsion and diluent, add the photoinitiator, stir, add the modified graphite phase carbon nitride and pigment, stir ultrasonically, grind, and obtain a protective coating; mix the long-chain alkyl-modified polysilazane and 50 mL of toluene, heat to 82°C, add 0.4 g of azobisisobutyronitrile and 20 mL of toluene, keep warm for 12 hours, vacuum distill, wash, rotary evaporate, and dry to obtain modified graphite phase carbon nitride;

[0009] The preparation of the composite waterborne polyurethane emulsion comprises the following steps:

[0010] 1) 2.4 g of a long-chain alkyl-modified polysilazane containing a double bond, 1 g of 2-mercaptoethanol, 6.8 mg of 2-hydroxy-2-methylpropiophenone, and 20 mL of chloroform were mixed and treated with ultraviolet light to obtain a hydroxylated long-chain alkyl-modified polysilazane; the working conditions for the ultraviolet light treatment were: the light intensity was 20 mW / cm2 , time is 110min;

[0011] 2) Under a nitrogen atmosphere, 6 g of isophorone diisocyanate, 10 μL of dibutyltin dilaurate, and 5.6 g of castor oil were mixed, the temperature was raised to 68° C. and kept warm for 2 h, 0.8 g of 3-dimethylamino-1,2-propylene glycol was added, and stirring was continued for 2 h, a mixed solution of 1.4 g of 2,2-dihydroxymethylpropionic acid and 10 mL of acetone was added, the temperature was raised to 72° C. and kept warm for 1 h, 0.6 g of hydroxylated long-chain alkyl-modified polysilazane was added, the temperature was lowered to 62° C. and stirred for 1 h, 1 g of hydroxyethyl methacrylate was added, and the temperature was lowered to 35° C., 0.5 g of glacial acetic acid was added, and the mixture was stirred for 30 min, deionized water was added for emulsification, and rotary evaporation was performed to obtain a composite waterborne polyurethane emulsion with a solid content of 25%;

[0012] The preparation of the double-bond-containing long-chain alkyl-modified polysilazane comprises the following steps:

[0013] A. Under argon atmosphere, 1 mmol of hexamethylene diisocyanate and 20 mL of tetrahydrofuran were mixed, 1 mmol of n-hexadecanol and 0.4 mg of dibutyltin dilaurate were added, the temperature was raised to 42°C and kept for 4 hours, and rotary evaporated to obtain an isocyanate-based long-chain alkyl compound;

[0014] B. Mix 1 g of vinyl polysilazane and 10 mL of tetrahydrofuran, add 0.8 g of an isocyanate-based long-chain alkyl compound, raise the temperature to 42° C. and keep the temperature for 8 h, and rotary evaporate to obtain a long-chain alkyl-modified polysilazane containing a double bond;

[0015] S3: spraying the protective coating on the surface of the pretreated towel rack, light curing, and drying to obtain a towel rack.

[0016] Comparative Example 1: Taking Example 3 as the control group, the modified graphite phase carbon nitride was replaced by graphite phase carbon nitride, and the other processes were normal.

[0017] Comparative Example 2: Example 3 was used as a control group, hydroxylated long-chain alkyl-modified polysilazane was not prepared, and other processes were normal.

[0018] Comparative Example 3: Example 3 was used as a control group, and no long-chain alkyl-modified polysilazane containing double bonds was prepared, and other processes were normal.

[0019] Comparative Example 4: Example 3 was used as the control group, and no spraying treatment was performed. The protective coating was directly coated on the surface of the pretreated towel rack, and other processes were normal.

[0020] The protective coating formed on the pretreated towel rack surface after curing has a thickness of 50 μm.

[0021] Sources of raw materials used (for demonstration purposes only):

[0022] Towel rack: Its chemical composition is as follows: carbon 0.03%, silicon 1.1%, manganese 2%, chromium 17.8%, nickel 10.5%, sulfur 0.01%, and the balance is iron; photoinitiator 184 (99%): Hubei Zhenbo Chemical Co., Ltd.; pigment (CI pigment white 5, industrial grade): Pandex (Shanghai) International Trade Co., Ltd.; polyethylene glycol octylphenyl ether 2021523: Hubei Chengfeng Chemical Co., Ltd.; vinyl polysilazane 503590-70-3: Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.; isobornyl acrylate I102358, 1,6-hexanediol diacrylate H102721, tyrosine T121349, thiourea T112512, vinyl triethoxy Silane T103647, azobisisobutyronitrile A434183, 2-mercaptoethanol M468050, 2-hydroxy-2-methylpropiophenone H110280, isophorone diisocyanate I109582, dibutyltin dilaurate D100274, castor oil C110663, 3-dimethylamino-1,2-propanediol D135042, 2,2-dihydroxymethylpropionic acid B104539, hydroxyethyl methacrylate H103044, hexamethylene diisocyanate H106723, tetrahydrofuran T103263, n-hexadecanol H103405: ​​Aladdin reagent; sodium bicarbonate, zinc acetate, ethanol, toluene, chloroform, acetone, glacial acetic acid, analytical grade: Sinopharm reagent.

[0023] Performance test: The towel racks prepared in the embodiments and comparative examples were tested:

[0024] Hydrophobicity: The water contact angle was characterized by using a tester, and a 3μL deionized water droplet was used for the test; Antibacterial property: Staphylococcus aureus was used as the test strain, and the plate method was used for the test; Adhesion: The hundred-grid method was used for the test, and a hundred grids were drawn on the coating surface at equal intervals. The scratches needed to expose the substrate, and the tape was attached to it and then detached from the tape at a uniform speed. Rating standards: Grade 0-no edge shedding, Grade 1-cross damaged area less than 5%, Grade 2-cross damaged area less than 15%, Grade 3-cross damaged area less than 35%; Corrosion resistance: The towel rack was kept at 300℃ for 3h, cooled and immersed in a sodium chloride solution with a mass concentration of 8% for 48h to observe the surface corrosion morphology. If there was no blistering or damage, it was excellent, otherwise it was unqualified; the results are shown in Table 1;

[0025] Table 1

[0026] Contact angle (°) Antibacterial rate (%) Adhesion(grade) Corrosion resistance Example 1 152.6 99.8 0 excellent Example 2 152.7 99.9 0 excellent Example 3 152.9 99.9 0 excellent Comparative Example 1 148.1 87.1 1 Failure Comparative Example 2 149.3 94.2 1 Failure Comparative Example 3 147.8 85.3 1 Failure Comparative Example 4 / / 1 /

[0027] The present invention provides a process for anti-corrosion spraying on the surface of a towel rack. By limiting the composition and process, a towel rack with high mechanical strength, super hydrophobicity, antibacterial, high temperature resistance and corrosion resistance is prepared, which greatly extends the service life of the towel rack. In Table 1, / indicates that the item has not been tested.

[0028] By comparing Example 3 with Comparative Example 1 and Comparative Example 3, it can be seen that graphite phase carbon nitride with the advantages of small particle size, high physicochemical stability, and barrier effect for the penetration of corrosive ions is introduced into the protective coating as a filler to improve the corrosion resistance of the coating. Tyrosine and thiourea are used as precursors, and graphite phase carbon nitride nanosheets are prepared by a microwave method. Then, the prepared graphite phase carbon nitride nanosheets are doped by a hydrothermal method to obtain zinc oxide-graphite phase carbon nitride binary composite nanomaterials, thereby greatly improving its photocatalytic and antibacterial properties; in order to improve the uniformity of dispersion of composite graphite phase carbon nitride in the protective coating and improve the adhesion between the composite graphite phase carbon nitride and the coating, In order to improve the bonding strength, vinyl triethoxysilane is used to double-bond the composite graphite phase carbon nitride, and then free radical polymerization is used to graft long-chain alkyl-modified polysilazane containing double bonds, thereby giving the modified graphite phase carbon nitride excellent hydrophobicity. The long-chain alkyl-modified polysilazane containing double bonds is prepared by first reacting n-hexadecanol with hexamethyl diisocyanate to synthesize a long-chain alkyl compound with an isocyanate group, which is then condensed and coupled with vinyl polysilazane. At the same time, the anchoring properties of polysilazane are used to improve its bonding strength with the substrate towel rack, so that it is firmly attached to the surface of the towel rack, giving the towel rack excellent hydrophobicity, antibacterial properties, thermal stability and corrosion resistance.

[0029] By comparing Example 3 with Comparative Examples 2 and 3, it can be seen that in order to comply with the green development route, the present invention uses bio-based polyol castor oil as a raw material, and synthesizes a prepolymer together with isophorone diisocyanate under the action of a catalyst. In order to further improve the antibacterial property of the towel rack, 3-dimethylamino-1,2-propylene glycol is used as a chain extender, and then glacial acetic acid is used to neutralize the tertiary amine in the system to give the coating a quaternary ammonium salt group; 2,2-dihydroxymethylpropionic acid is used as a hydrophilic chain extender, hydroxyethyl methacrylate is used as a capping agent, and a hydroxylated long-chain alkyl-modified polysilazane prepared by a photoclick reaction of a long-chain alkyl-modified polysilazane containing a double bond and 2-mercaptoethanol is introduced as a capping agent, which greatly improves the bonding strength between the coating and the towel rack, improves the water resistance and high temperature resistance of the coating, and extends the service life of the towel rack.

[0030] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A corrosion-resistant spraying process for the surface of a towel rack, characterized in that: The following steps are involved: S1: frosting, polishing, cleaning and drying the towel rack in sequence to obtain a pre-treated towel rack; S2: mixing the composite waterborne polyurethane emulsion and the diluent, adding the photoinitiator, stirring, adding the modified graphite phase carbon nitride and the pigment, ultrasonically stirring, grinding, and obtaining a protective coating; S3: spraying the protective coating on the surface of the pretreated towel rack, light curing, and drying to obtain a towel rack.

2. The corrosion-resistant spraying process for the surface of a towel rack according to claim 1 is characterized in that: The protective coating comprises, by weight, 40-48 parts of composite waterborne polyurethane emulsion, 10-12 parts of diluent, 1-1.2 parts of photoinitiator, 3-7 parts of modified graphite phase carbon nitride and 1-3 parts of pigment.

3. The corrosion-resistant spraying process for the surface of a towel rack according to claim 1 is characterized in that: The diluent is one or a combination of carboxyl acrylate, isobornyl acrylate, 1,6-hexanediol diacrylate and dipropylene glycol diacrylate.

4. The corrosion-resistant spraying process for the surface of a towel rack according to claim 1 is characterized in that: The working conditions of the light curing treatment are: the light source is a 1000W high-pressure mercury lamp, the distance from the light source is 28-30cm, and the time is 4-6min.

5. The corrosion-resistant spraying process for the surface of a towel rack according to claim 1 is characterized in that: The working conditions of spraying are: compressed air pressure of 0.6MPa, flow rate of 0.3mL / s, and moving speed of 3.5cm / s.

6. The corrosion-resistant spraying process for the surface of a towel rack according to claim 1 is characterized in that: The preparation of the modified graphite phase carbon nitride comprises the following steps: (1) tyrosine, thiourea and deionized water are mixed, microwaved at 800 W for 3 min, cooled, heated to 550° C. and kept warm for 2 h, washed, dried, added with deionized water, ultrasonically peeled for 3-4 h, centrifuged and dried to obtain graphite phase carbon nitride nanosheets; sodium bicarbonate solution and polyethylene glycol octylphenyl ether are mixed, stirred for 20-30 min, zinc acetate solution is added, stirring is continued for 50-60 min, graphite phase carbon nitride nanosheets are added, stirring is continued for 110-120 min, allowed to stand, filtered, washed, dried, ground, heated to 250° C. and calcined for 3 h, ground to obtain composite graphite phase carbon nitride; (2) mixing composite graphite phase carbon nitride, anhydrous ethanol and deionized water, stirring ultrasonically for 20-30 minutes, heating to 78-82° C., adding vinyl triethoxysilane, stirring for 2-3 hours, centrifuging, washing, drying and grinding to obtain double-bonded composite graphite phase carbon nitride; (3) Under nitrogen protection, double-bonded composite graphite phase carbon nitride, long-chain alkyl-modified polysilazane containing double bonds, and toluene are mixed, the temperature is raised to 78-82° C., a mixed solution of azobisisobutyronitrile and toluene is added, the mixture is kept warm for 10-12 hours, and vacuum distillation, washing, rotary evaporation, and drying are performed to obtain modified graphite phase carbon nitride.

7. The corrosion-resistant spraying process for the surface of a towel rack according to claim 1 is characterized in that: The preparation of the composite waterborne polyurethane emulsion comprises the following steps: (1) mixing a long-chain alkyl-modified polysilazane containing a double bond, 2-mercaptoethanol, 2-hydroxy-2-methylpropiophenone, and chloroform, and treating the mixture with ultraviolet light to obtain a hydroxylated long-chain alkyl-modified polysilazane; (2) Under a nitrogen atmosphere, isophorone diisocyanate, dibutyltin dilaurate and castor oil are mixed, the temperature is raised to 63-68°C and kept warm for 2-3 hours, 3-dimethylamino-1,2-propylene glycol is added, and stirring is continued for 1-2 hours, a mixed solution of 2,2-dihydroxymethylpropionic acid and acetone is added, the temperature is raised to 68-72°C and kept warm for 1-2 hours, hydroxylated long-chain alkyl modified polysilazane is added, the temperature is lowered to 58-62°C and stirred for 1-2 hours, hydroxyethyl methacrylate is added, the temperature is lowered to 30-35°C, glacial acetic acid is added, and stirring is continued for 15-30 minutes, deionized water is added for emulsification, and rotary evaporation is performed to obtain a composite waterborne polyurethane emulsion.

8. The corrosion-resistant spraying process for the surface of a towel rack according to claim 7 is characterized in that: The working conditions of UV treatment are: light intensity is 18-20mW / cm 2 , time is 110-130min.

9. A corrosion-resistant spraying process for the surface of a towel rack according to claim 6 or 7, characterized in that: The preparation of the double-bond-containing long-chain alkyl-modified polysilazane comprises the following steps: A. Under an argon atmosphere, hexamethylene diisocyanate and tetrahydrofuran are mixed, n-hexadecanol and dibutyltin dilaurate are added, the temperature is raised to 38-42°C and kept for 4-6 hours, and rotary evaporation is performed to obtain an isocyanate-based long-chain alkyl compound; B. Mix vinyl polysilazane and tetrahydrofuran, add isocyanate long-chain alkyl compound, raise the temperature to 38-42° C. and keep warm for 8-10 hours, and rotary evaporate to obtain long-chain alkyl modified polysilazane containing double bonds.

10. A towel rack, characterized in that: The invention is prepared by the process according to any one of claims 1 to 8.

Citation Information

Cited By

  • Aerospace bearing wear-resistant coating based on polysilazane and preparation method thereof

    CN120272107A